Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and the Yahoo Answers website is now in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Solve using the quadractic formula x^2+4x+6=0?
thank you
4 Answers
- Anonymous1 decade agoFavorite Answer
Here, by ax² + bx + c = 0, we have:
a = 1
b = 4
c = 6
Then by quad. formula..
x = (-b ± √(b² - 4ac))/2a
= (-4 ± √(4² - 4 * 1 * 6))/2
= (-4 ± √(16 - 24))/2
= (-4 ± √(-8))/2
= (-4 ± 2i√2)/2
= -2 ± i√2
I hope this helps!
Source(s): Knowledge - ?Lv 51 decade ago
a = 1
b = 4
c = 6
Just plug those into the formula and simplify.
edit: Looks like I said the same thing as above, except slower. :)
- Randy PLv 71 decade ago
a = 1
b = 4
c = 6
Just plug them into the formula x = [-b +- sqrt(b^2 - 4ac)]/2a. Where are you having difficulty?
- Anonymous1 decade ago
-b(+/-) (sqrt)[b^2 -4ac) /(2a)
b=4
a=1
c=6
plug in and solve.